Paternal and maternal socialization perception on adolescent resilience - Axpe, Inge; Fernández-Zabala, Arantza; Goñi Palacios, Eider; Ramos-Díaz, Estibaliz (Anales de Psicología / Annals of Psychology, 2023)
Parent-child relations are a key aspect in adolescent development, since feelings of parental acceptance or rejection have been found to be associated with teenagers’ psychological adjustment. Resilience, usually conceptualised as the ability to manage or adapt to challenges and adversity, is a fundamental factor in adjustment during adolescence, a period characterised by numerous simultaneous changes and challenges in different aspects of life. The aim of the present study is therefore to analyse the predictive capacity of different dimensions of parental socialisation (affection-communication and criticism-rejection) on adolescent resilience. Method: Participants were 899 adolescents (50.4% female), aged 12 to 19 years (M = 14.68; SD = 1.73). Linear regressions were performed to analyse the predictive capacity of the different dimensions of parental socialisation on adolescent resilience. Results: Paternal dimensions, especially paternal criticism-rejection, were revealed as relevant factors for predicting resilience scores. Discussion: The results point to the important impact of the criticism-rejection felt by adolescents, especially if perceived from the father. Different possible interpretations of these dimensions are discussed, in accordance with whether they are perceived from the mother or the father.